Differences between dental health service quality and utilization of Community Health Centres in the City of Padang based on indicators of utilisation effectiveness - Darma, Azri; Hidayati, Hidayati; Oenzil, Fadil (Padjadjaran Journal of Dentistry, 2018)
Introduction: The high prevalence of oral disease have not been followed by the availability of oral healthcare, especially at the community-based level. This study was aimed to determine the differences between dental health service quality and utilisation of community health centres in the city of Padang based on indicators of utilisation effectiveness. Methods: A cross-sectional survey was conducted towards two Community Health Services (Puskesmas) as the samples selected using random sampling technique. One Community Health Service was representing a rarely visited Community Health Service with ≤ 9 patients visit per day, and another Community Health Service was representing oppositely. As much as 131 respondents were included in this study, selected using the purposive sampling method. Dimensional satisfaction of service quality including tangibility, reliability, responsiveness, assurance, and empathy, were collected by interviewing the respondents based on a self-reported questionnaire. All data were analysed using the chi-square test. Results: The majority of respondents agreed that dimensional satisfaction such as tangibility, reliability, responsiveness, assurance, and empathy at both Community Health Services were at a good level. There was a significant relationship (p < 0.05) between several dimensional satisfaction of service quality variables (the wide and clean parking area; intense involvement of dentists on every oral examination; friendly service by the front-office; and empathetic affection of dentists towards the patient’s complain) and the utilisation of oral health services. Conclusion: No service differences found from relationship analysis between dental health service quality and utilisation of community health centres in the city of Padang based on indicators of utilisation effectiveness.Keywords: Service quality, dimensional satisfaction, oral health service, service utilisation, Community Health Centre.